2015
DOI: 10.1021/acs.orglett.5b00123
|View full text |Cite
|
Sign up to set email alerts
|

Pressocucurbit[5]uril

Abstract: A novel macrocycle, decamethylpressocucurbit[5]uril (Me10prCB[5]), was synthesized by acid-catalyzed condensation of propanediurea and paraformaldehyde. This macrocycle binds methane with higher affinity than cucurbit[5]uril and its permethylated derivative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…[64][65][66][67] The isolation of first prCB, the Me-prCB [5] was reported simultaneously by Sindelar [64] and Wang. [64][65][66][67] The isolation of first prCB, the Me-prCB [5] was reported simultaneously by Sindelar [64] and Wang.…”
Section: Chain Cycle Equilibriummentioning
confidence: 95%
See 3 more Smart Citations
“…[64][65][66][67] The isolation of first prCB, the Me-prCB [5] was reported simultaneously by Sindelar [64] and Wang. [64][65][66][67] The isolation of first prCB, the Me-prCB [5] was reported simultaneously by Sindelar [64] and Wang.…”
Section: Chain Cycle Equilibriummentioning
confidence: 95%
“…[66] The templated synthesis of prCB [4] and prCB [5] was demonstrated in the presence of Ca 2 + in 23 % yield and Ba 2 + in 20 % yield, respectively (Table 2, lines 7 and 8). [64] The presence of Ca 2 + and Ba 2 + salts induced the precipitation of 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 macrocycles from the reaction mixture in a 1 : 2 complex, with metals bound to prCBs at the portals ( Figure 6). [64] The presence of Ca 2 + and Ba 2 + salts induced the precipitation of 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 macrocycles from the r...…”
Section: Chain Cycle Equilibriummentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, cucurbiturils are known as the artificial hosts with the highest binding affinities toward neutral and cationic organic guests in water. Acyclic cucurbituril derivatives have been studied by our group and that of Isaacs in order to further explore the mechanism of cucurbituril formation and also to design host molecules with more flexible structures in comparison with cucurbiturils. This paper focuses on molecular clips formed by glycoluril dimers and framed by aromatic sidewalls. Recently, it was shown that the glycoluril units in the cucurbituril structure can be replaced by propanediurea. This inspired us to investigate whether the substitution of propanediurea for glycoluril was also possible in glycoluril dimers and how the substitution would affect the supramolecular properties of the resulting host molecules. Here, we present our results.…”
Section: Introductionmentioning
confidence: 99%